ЧОТИРИТЕРМІНАЛЬНІ АКСІАЛЬНІ ПОДВІЙНО-ЕКРАНОВАНІ ВИМІРЮВАЛЬНІ КОЛА - Міхаль, О.О. (Інститут електродинаміки НАН України, Київ, 2022)
An impedance measurement object with an H-shaped four-terminal equivalent substitution circuit is considered. An error analysis was performed for sensors whose non-informative supply resistances are of the same order or exceed the measured impedance. A new definition of four-terminal impedance has been proposed, namely four-terminal axial be-shielded (FTABS) measuring object. Based on such new definition, the scheme of axial-bishielded bridges is proposed for precision measurement of temperature and electrolytic conductivity of liquids. Such bridges differ from the well-known coaxial bridges since the former ones have an additional circuit for equipotential protection, which is located between the flow circuits of direct and reverse currents. References 18, figures 7, tables 3.